Prevalence of developmental defects of enamel in children visiting a university hospital in Chennai - a retrospective study - DEVI.G, KARTHIGA; MANI, GEO; PRADEEP D, (The journal of contemporary issues in business and government, 2020)
The developmental defects of the enamel (DDE) may be the alternation of enamel that may affect an area of one surface or may be widespread affecting all the surface of the teeth. Early diagnosis of developmental defects of the enamel can prevent the child from having an impact on oral health. The aim of this study was to determine the prevalence of developmental defects of enamel in children visiting a university hospital in the Chennai population. This was a retrospective study done under a University setting. It was seen that 334 patients had Developmental Defects of Enamel. The data was collected from June 2019 to March 2020. The data was tabulated and entered in excel and the data was analysed using SPSS package software. The overall prevalence of the DDE was found to be 47%. The most common deformity was Hypoplasia (24.3%) and the least common deformity was Molar Incisal Demineralisation and Amelogenesis Imperfecta (0.9%). The most common tooth affected was maxillary left central incisor (5.1%) and the least common deformity was found in mandibular right first premolar and primary dentition (0.3%). There was a statistically significant association between DDE and buccal surface of teeth. It indicates the need for educating the population about the risk factors for the DDE.